Social Media Marketing, Consumer Engagement, and Organizational Equity in Indonesia’s Furniture Industry - Agustinus Purna Irawan; Sinta Paramita; Moehammad Gafar Yoedtadi; Wulan Purnama Sari; Eunice Mareth Querol Areola (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2026)
Social media has become an essential element of digital transformation, encouraging organizations to use social media as a strategic communication instrument to build relationships with stakeholders. Although previous studies have widely examined the effectiveness of social media marketing in commercial companies, research on its use in industrial association organizations remains limited. This study aims to analyze the influence of social media marketing on consumer engagement and organizational equity in the Indonesian furniture industry association context. This research employed a quantitative approach with an explanatory survey design. Data were collected through questionnaires distributed to followers of ASMINDO’s official Instagram account who met the research criteria. The research instrument was measured using a six-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that social media marketing has a positive and significant effect on consumer engagement and organizational equity. These results suggest that digital communication activities through Instagram not only enhance audience engagement but also strengthen positive perceptions of the organization as a representation of the Indonesian furniture industry. This study extends the application of social media marketing concepts to industrial association organizations and highlights organizational equity as a strategic outcome of organizational digital communication.